No Differences in Motor Units Discharge Rate Between Females and Males in Explosive Ankle Dorsiflexions - Grootenhuis, Anna; Hiereth, Fiona C.; Škarabot, Jakob; Oßwald, Marius; Del Vecchio, Alessandro; Gruber, Markus; Ruggiero, Luca (Scandinavian journal of medicine & science in sports, 2025)
Males and females exhibit comparable levels of explosive strength if the rate of torque development (RTD) is considered relative to the maximal voluntary isometric torque (MVT). Given the greater proportion of type I to type II fibers area in muscles of females than males ( 20% in tibialis anterior muscle), with slower contractile kinetics, the discharge rate of motor units (MUDR) in explosive efforts may be higher to compensate for the slower muscle contractile properties. Yet, it is to date unknown whether sex differences in MUDR in explosive efforts exist. Twenty-two females and 12 males (20–34 years) performed electrically evoked and voluntary rapid isometric ankle dorsiflexions. Electrically evoked contractions consisted of three trains of 50 supramaximal stimuli at the common peroneal nerve at 200 Hz. Ten voluntary explosive contractions were then performed while recording high-density electromyography signals from the tibialis anterior. No significant differences were reported between males and females for both voluntary and electrically evoked relative peak RTD (8.0 ± 2.0 vs. 7.7 ± 0.8 and 6.4 ± 0.7 vs. 6.1 ± 2.1 MVT s−1), and for RTD and muscle activity throughout the first 150 ms (p > 0.07). Despite no significant differences, these metrics were not equivalent between sexes when assessed with equivalence testing. Time to peak RTD was shorter in males than females for both contraction types (voluntary: 61 ± 12 vs. 74 ± 14 ms; electrically evoked: 24 ± 3 vs. 28 ± 7 ms; p < 0.01). MUDR at the beginning of the explosive voluntary efforts was not different between sexes (males: 61 ± 15; females: 67 ± 16 Hz; p < 0.23). Overall, despite known sex-related differences within the skeletal muscle, the control of rapid torque production is not different between sexes.
CRIS-Team Scopus Importer:2025-05-23
Keywords: ballistic; EMG decomposition; firing rate; motoneurones; rapid; sex differences